2013
DOI: 10.13033/isahp.y2013.037
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Malaysian Graduate Employability Skills: Quality Function Deployment Approach

Abstract: In the challenging economic world, employers are looking for graduates employees who are able drive organization to compete successfully in the market. Graduates should equip themselves with relevant employability skill as needed by the recent employers. Besides that, higher education institutions must evaluate the effectiveness of employability skills development approaches on graduates' employability skills. The main objectives of this study are to identify the important of Malaysian graduates' employability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 9 publications
1
2
0
Order By: Relevance
“…While item 3 (the ability to work toward agreements involving the exchange of opinions and resolve divergent issues) has the lowest mean score (m = 4.54; SD = .720) The overall mean score as well the mean scores for each item in this dimension indicate that the respondents have a high level of awareness on the interpersonal skills as part of GE skills. This is in accordance with Warraich and Ameen (2010); Hamid et al (2013) who state that employers seek graduates who have six dimensions of employability skills, which include interpersonal skills. As shown in Table 6, Information Technology Skills has an overall mean score of 4.38 (SD = .755).…”
Section: Findings and Discussionsupporting
confidence: 86%
“…While item 3 (the ability to work toward agreements involving the exchange of opinions and resolve divergent issues) has the lowest mean score (m = 4.54; SD = .720) The overall mean score as well the mean scores for each item in this dimension indicate that the respondents have a high level of awareness on the interpersonal skills as part of GE skills. This is in accordance with Warraich and Ameen (2010); Hamid et al (2013) who state that employers seek graduates who have six dimensions of employability skills, which include interpersonal skills. As shown in Table 6, Information Technology Skills has an overall mean score of 4.38 (SD = .755).…”
Section: Findings and Discussionsupporting
confidence: 86%
“…Normally, graduates tend to fail because they do not demonstrate this marketability and by only showing their academic merit (Ali et al, 2018). Some of the skills required are such as verbal and written communication, problem solving, teamwork, personal qualities, leadership, analytical and also technical skills (Suleman, 2016;Hamid et al, 2013). These skills can be categorized into five dimensions which are: (1) application skill; (2) self-efficacy; (3) metacognition; (4) entrepreneurship skill and (5) soft-skill (Ali et al, 2018).…”
Section: Literature Review Graduate Employability (Ge) In Malaysiamentioning
confidence: 99%
“…In terms of the employability skills development, Hamid et al (2013) found that the most effective approach for employability skills development is work integrated learning. This followed by stand alone subject model, academic support programme, embedded subject model, non-academic support programme and the least is campus life activities.…”
Section: Literature Review Graduate Employability (Ge) In Malaysiamentioning
confidence: 99%